2020
DOI: 10.1109/access.2020.2971588
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis of the Short-Arc Initial Orbit Determination

Abstract: The solution of the short-arc angles-only orbit determination problem has large uncertainty because the topocentric range is not observable. For a certain angular observation tracklet with measurement noise, there exist numerous potential orbits, all of which are compatible with the observations. However, the solution of a deterministic initial orbit determination algorithm is usually far different from the true orbit, especially for the semimajor axis and the eccentricity. A new sampling method is proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It is important to place the initial solution evenly in the problem area for improving the performance of heuristic algorithms for various optimization problem such as random forest [20], [21], [22], [23], [24]. The location of the optimal point is generally unknown and when the normal sampling method in the problem area is used, it is difficult to evenly distribute the initial solution.…”
Section: B Latin Hypercube Samplingmentioning
confidence: 99%
“…It is important to place the initial solution evenly in the problem area for improving the performance of heuristic algorithms for various optimization problem such as random forest [20], [21], [22], [23], [24]. The location of the optimal point is generally unknown and when the normal sampling method in the problem area is used, it is difficult to evenly distribute the initial solution.…”
Section: B Latin Hypercube Samplingmentioning
confidence: 99%
“…The traditional method of initial orbit determination is to solve the parameter estimation problem for conic curves under perturbation conditions, that is, the spacecraft's orbit in space can be approximated as a conic curve [5]. However, for a continuous thrust spacecraft, its orbit in space cannot be described by a conic curve, the unknown thrust acceleration increases the dimension of the problem, and the traditional initial orbit determination algorithm [6] is no longer applicable. JianRong Chen et al [7] used the simplex method to solve the orbit determination problem of a continuous small-thrust maneuvering satellite based on the start and end times of electric propulsion control.…”
Section: Introductionmentioning
confidence: 99%
“…Sciré et al showed that the batch estimators could be a useful tool to estimate the state of space debris at a certain time [24]. Tao et al presented a more accurate IOD method [25], namely the Laplace-LS orbit determination method, whose estimation variance is close to the Cramer-Rao Lower Bound (CRLB). It can be used when the observation arc is very short or the sensor has limited accuracy.…”
Section: Introductionmentioning
confidence: 99%